Thermodynamic evaluation of hydrogen production for fuel cells by using bio-ethanol steam reforming: Effect of carrier gas addition (2009)
Omitting the influence of the addition of carrier gas to the reaction system for hydrogen production by bio-ethanol steam reforming can lead to wrong conclusions, especially when it is going to be made to scale. The effect of carrier gas addition to produce hydrogen using bio-ethanol steam reforming to feed fuel cells was evaluated. Thermodynamic calculations in equilibrium conditions were made, however the analysis derived from them can also be applied to kinetic conditions. These calculations were made by using the Aspen-HYSYS software at atmospheric pressure and different values of temperature, water/ethanol molar ratios, and inert (argon)/(water/ethanol) molar ratios. The addition of inert carrier gas modifies the concentrations of the reaction products in comparison to those obtained without its presence. This behavior occurs because most of the reactions which take place in bio-ethanol steam reforming have a positive difference of moles. This fact enhances the system sensitivity to inert concentration at low and moderated temperatures (<700 °C). At high values of temperature, the inert addition does not influence the composition of the reaction products because of the predominant effect of inverse WGS reaction.